Compressed and Crumpled Porous Carbon Electrode for High Volumetric Performance Electrical Double‐Layer Capacitors. Issue 6 (15th April 2019) - Guo, Hongshuai; Ding, Bing; Dong, Xiaowan; Dong, Shengyang; Zhang, Yadi; Zhu, Jiajia; Dou, Hui; Zhang, Xiaogang
Abstract : The 2D carbon sheets have great potential for the construction of compact electrodes with high volumetric performance for electrical double‐layer capacitors (EDLCs), by virtue of their excellent electrical conductivity, high exposed surface area, free of interpores, and unimpeded ion‐diffusion channels. However, 2D nanosheets restack and aggregate during the preparation processes of electrodes, reducing available surface area, and limiting transport of ions. Herein, a facile and scalable method is presented to prepare highly porous crumple carbon balls (PCCBs) assembled by 2D carbon nanosheets. Such a unique nanostructure endows the PCCB electrode with large electrolyte‐accessible surface area and short ion‐diffusion pathways even when compressed at 40 MPa. Electrochemical evaluations in 1‐ethyl‐3‐methylimidazolium tetrafluoroborate (EMIMBF4 ) electrolyte indicate that the compressed PCCB electrodes still show superior gravimetric (103 F g −1 ) and volumetric capacitances (127 F cm −3 ) at 1 A g −1 . The highest volumetric energy density of symmetrical EDLC based on compressed PCCB‐based electrode is 53.9 Wh L −1 . This work provides a new direction for the development of high volumetric energy density carbon‐based EDLCs. Abstract : Porous crumple carbon balls (PCCBs) assembled from 2D carbon sheet material are obtained with excellent packing density, high ion‐accessible surface area, and short ion‐diffusion pathways using an aerosol drying device. The PCCB electrodes pressured at 40 MPa show an increase in the density (1.23 g cm −3 ). The volumetric energy density of PCCB‐based EDLC devices can reach 53.9 Wh L −1 .